Orthopedic and Nonsurgical Orthodontic Treatment of Adolescent Skeletal Class III Malocclusion Using Bone-Anchored Maxillary Protraction and Temporary Anchorage Devices: A Case Report - Mohammed Alnefaie; Woo-Jin Han; Yoon-Soo Ahn; Won-Kyeong Baik; Sung-Hwan Choi (MDPI AG, 2022)
This report describes the case of a 12-year-old female patient with a long mandible experiencing difficulty chewing with the right molar. Considering the age of the patient, bone-anchored maxillary protraction using four miniplates placed below the maxillary zygomatic arch and anterior symphysis of the mandible and Class III intermaxillary elastics were planned. After 12 months, orthodontic treatment was initiated. After extraction of the impacted maxillary right second premolar and mandibular right second primary molar, protraction of the mandibular right molars was performed using a miniplate placed on the anterior part of the mandible as an anchor. Miniscrews were placed in the left posterior part of the mandible to improve the molar relationship and correct the dental midline through distalization of the mandibular left posterior teeth. We reported successful sequential comprehensive nonsurgical treatment in an adolescent with skeletal Class III malocclusion.